Breaking out again : feminist ontology and epistemology - Stanley, Liz, 1947- (New York : Routledge, 1993)
In this new edition, the authors treat the book's previous reception in terms of academic feminism, reviewing developments in feminist thinking on research issues. They then examine how we know and construct the world based on differing ethics, histories, races and sexualities.